Exploring Studies of Information Security Culture in Malaysia - Nasir, Akhyari; Ruzaini, Abdullah Arshah; Mohd Tamizan, Abu Bakar (2016)
security management in terms of improving employees’ security behavior in dealing with information assets. Many studies have been done to explore and investigate ISC in various aspects including the concepts, factors, challenges and particular applications related to assessment of ISC in an organization. However, there is no an indication on the current status of ISC studies that have been done in Malaysia. This paper will discuss these matters to provide a clear picture of the ISC studies in Malaysia and analyze particular areas that need to be further explored. It revealed that there are many areas and issues still not being comprehensively examined and series of studies need to be done so that better solutions relating to the ISC issues in Malaysian organization could be formulized.